On arschkriecher, arschaffen, assholes and dumbasses – (breaking) taboos of the German lexeme arsch and the Polish lexeme dupa (on the basis of lexicographical research) - Szczęk, Joanna (Acta Universitatis Lodziensis. Folia Germanica, 2017)
This article presents a lexical analysis of the German lexeme Arsch and the Polish lexeme dupa. The departure point is the thesis that linguistic taboos connected with this vulgarism are more and more often broken. This can be observed in the numerous examples given in the text and the formative and collocational potential of the analyzed lexemes.